VALIDITY AND RELIABILITY TEST DENTISTRY AND HIV/AIDS STIGMA SCALE INDONESIAN VERSION IN DENTAL AND ORAL HEALTH SERVICES - Tasya Naftha Niella Agustin; Rochman Mujayanto; Musri Amuwarningsih (Jurnal Medali, 2023)
Background: People with HIV/AIDS experience stigma which results in social devaluation in various ways. Stigma received in the form of prejudice, shame, isolation, rejection, and discrimination against people who are believed to have the disease. Prejudice and discriminatory behavior on the part of dental health care workers are significant barriers to normal dental health care for people living with HIV/AIDS. A measuring tool to determine the stigma of HIV/AIDS in dental and oral health care, using instrument Dentistry and HIV/AIDS Stigma scale. The instrument used English as the introduction. The researcher wants to translate the instrument into the Indonesian version and determine the validity and reliability of the instrument. Method: The validity and reliability test used a sample of 50 people with HIV/AIDS, using non-probability sampling and consecutive sampling techniques. The research stages were instrument translation, instrument back translation, validity test with test Pearson correlation (r count > r table) and reliability test by looking at the value Cronbach alpha (> 0.7). Result: At the translation stage there were several word changes with adaptation and cultural adjustments in Indonesia. The validity test stage showed the correlation value of each item was greater than 0.278 and the reliability stage showed the Cronbach alpha value of 0.897 which was greater than 0.7. Conclusion: It can be concluded that instrument Dentistry And HIV/AIDS Stigma Scale Indonesian version valid and reliable, to be used to measure the perceptions and attitudes of people with HIV/AIDS towards the dental and oral health services they receive.